KAsH score beyond myocardial infarction: a new risk stratification tool for myocardial injury?. (25th November 2020) - Sousa, J; Monteiro, J.P; Mendonca, F; Santos, M; Temtem, M; Neto, M; Alves, J; Andrade, G; Pereira, A; Freitas, S; Pereira, D.H; Mendonca, M.I; et al.
Abstract: Introduction: Our group has recently validated and published a new score - KAsH score. KAsH consists of a continuous, multiplicative score based on 4 simple clinical variables available at first medical contact, proven to be a robust predictor of in-hospital mortality and all-cause mortality at 1 year follow-up in patients with myocardial infarction, putting it next to other well established risk scores. However, the role of KAsH in patients with myocardial injury (Mi), a largely uncharacterized group in the literature, remains unknown. Purpose: We aim to assess the predictive power of KAsH in patients with myocardial injury (Mi), regarding in-hospital mortality and at 1 year follow-up. Methods: Prospective registry of 250 patients admitted consecutively through the emergency department from January 2018 onward, with higher than P99th high-sensitive troponin assay. The kit used was Roche's Elecsys hsSTAT, and the P99th appointed by the manufacturer was 14 ng/L. All patients with chronic kidney disease ClCr<15ml/min and myocardial infarction, were excluded from the analysis. We were left with 236 patients diagnosed with Mi. KAsH = (Killip Kimbal × Age × Heart Rate) / Systolic BP We used a simplified Killip classification: without heart failure (1 point), with heart failure (2 points) and in shock (3 points). We assessed the score's association to mortality and its predictive value through ROC curves and their respective area under the curve (AUC). Results: Both Killip and KAsH had a significant and positive association with in-hospital mortality (KK: p=0.02; KAsH: p<0.001) and cumulative mortality (KK: p=0.002; KAsH: p=0.008). In multivariate analysis, KAsH score as a continuous variable proved to be an independent predictor of in-hospital mortality (p=0.004) but not KK classification (p=0.96). We then categorized KAsH in its 4 different strata (1–4). Multivariate analysis indentified categorized KAsH as the only significant predictor of in-hospital mortality (OR 4.1, CI 2.1–8.1, p<0.001), with the predictive power of KAsH being even mildly superior (AUCs: KAsHcont 0.767, KAsHcat 0.743, KK 0.685). However, the same trend was not observed during follow-up, as none of them were significant predictors of mortality (all p>0.1). Conclusions: KAsH seems to maintain its in-hospital predictive value even in patients with Mi. To our knowledge, this is the first study that tries to apply risk scores and stratification tools to such a heterogeneous group of patients. By comprising hemodynamic variables, KAsH may actually be a better risk stratification tool than just the severity of heart failure on admission. However, unlike previously proven in myocardial infarction (MI), KAsH score and its hemodynamic variables do not seem to justify the high mortality on the long run behind these patients. More studies will be needed to address the complex causes behind long-term mortality of Mi patients. Funding Acknowledgement: Type of funding source: None